Staff Incentives and Project Implementation : Lessons from e-Government - World Bank (Washington, DC, 2012)
This note questions how would approaches to personnel management be changed, so that staff incentives facilitate-rather than undermine-project implementation. To succeed, institutional reform efforts must be supported by public officials. Electronic government (e-government) initiatives pose challenges typical of institutional reforms in public administration. Such initiatives also require addressing the scarce skills, and high costs of the information and communication technology sector. The note draws lessons from staff issues that impeded implementation of five e-government projects, and suggests how changes in personnel management can improve management of staff incentives.